EDUCATIONAL COMMUNICATION MANAGEMENT IN ADDRESSING ALGORITHMIC BIAS AND PUBLIC TRUST CRISIS: DIGITAL LITERACY AND AI ETHICS STRATEGIES IN INDONESIA’S DIGITAL DEMOCRACY ERA - Kusuma, Candra; Widiyanto, Widiyanto; Gautama, Sidartha Adi; Seneru, Wistina (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
The rapid advancement of artificial intelligence in Indonesia’s digital democracy has precipitated algorithmic bias and a public trust crisis, necessitating robust educational strategies. This study investigates the role of educational communication management, digital literacy, and AI ethics in mitigating these challenges and restoring institutional credibility. Employing an explanatory quantitative approach with Structural Equation Modelling (SEM), the research analyzed data from 100 purposively selected students to test the relationships between communication governance, algorithmic perception, and trust. The results reveal that educational communication management significantly enhances decision-making effectiveness (?= 0.397$), while AI ethics significantly positively influences public trust (?= 0.298). Conversely, algorithmic bias was found to substantially impact decision-making dynamics (? = 0.414). Interestingly, digital literacy demonstrated a positive yet statistically non-significant direct effect on trust variables. The study concludes that educational communication management and AI ethics are pivotal pillars for modern educational governance. To address the trust crisis and algorithmic distortions, educational institutions must implement transparent communication strategies integrated with ethical AI principles, thereby fostering an inclusive and accountable digital information ecosystem. ABSTRAK Kemajuan pesat kecerdasan buatan dalam demokrasi digital Indonesia telah memicu bias algoritmik dan krisis kepercayaan publik, sehingga memerlukan strategi pendidikan yang kuat. Studi ini menyelidiki peran manajemen komunikasi pendidikan, literasi digital, dan etika AI dalam mengurangi tantangan ini dan memulihkan kredibilitas institusional. Dengan menggunakan pendekatan kuantitatif eksploratif dengan Pemodelan Persamaan Struktural (SEM), penelitian ini menganalisis data dari 100 mahasiswa yang dipilih secara purposif untuk menguji hubungan antara tata kelola komunikasi, persepsi algoritmik, dan kepercayaan. Hasil penelitian menunjukkan bahwa manajemen komunikasi pendidikan secara signifikan meningkatkan efektivitas pengambilan keputusan (?= 0,397), sedangkan etika AI secara signifikan berpengaruh positif terhadap kepercayaan publik (?= 0,298). Sebaliknya, bias algoritmik ditemukan berdampak substansial pada dinamika pengambilan keputusan (? = 0,414). Menariknya, literasi digital menunjukkan pengaruh langsung yang positif namun secara statistik tidak signifikan terhadap variabel kepercayaan. Studi ini menyimpulkan bahwa manajemen komunikasi pendidikan dan etika AI merupakan pilar penting bagi tata kelola pendidikan modern. Untuk mengatasi krisis kepercayaan dan distorsi algoritmik, lembaga pendidikan harus menerapkan strategi komunikasi transparan yang terintegrasi dengan prinsip-prinsip AI yang etis, sehingga mendorong ekosistem informasi digital yang inklusif dan akuntabel.